Investigação do comportamento do câmbio nominal brasileiro em relação aos fundamentos econômicos baseados na Regra de Taylor - Miguens, Gabriel Perlott (2017)
The objective of this paper is to analyze the relationship between the Brazilian nominal exchange rate and the economic fundamentals, defined according to the Taylor rule. The transitory and permanent decomposition method was applied in order to identify how the model variables respond to transitory and permanent shocks. The interest is to identify how this relationship occurred during the floating exchange period. In Brazil, this occurred in 1999. At the same time, we try to verify evidence to consider that the fluctuations of the Brazilian nominal exchange rate do not follow a random walk process in the modern era of floating exchange rate. The results showed that the variables of the model are cointegrated and the transitory shocks play an important role in the Brazilian nominal exchange rate fluctuations while the permanent shocks are quite present in the fluctuations of the economic fundamentals of the model. Moreover, the results suggest that there is evidence that the Brazilian nominal exchange rate behavior should not be considered a random walk process.